2014
DOI: 10.1002/ccd.24987
|View full text |Cite
|
Sign up to set email alerts
|

Combined prospective United States clinical study data for the GORE® HELEX® septal occluder device

Abstract: The combined clinical study cohort represents the largest prospective, controlled clinical trial data set available for the GORE(®) HELEX(®) Septal Occluder. The clinical data presented in this report reaffirm the safety and efficacy of the GORE(®) HELEX(®) Septal Occluder when utilized for secundum atrial septal defect repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(43 reference statements)
3
7
0
Order By: Relevance
“…Migration of the device along with erosion of the aorta during follow-up was detected in 18 out of 15,900 (0.12% or 1 in 1,000) ASO implantations in a US study 45 , 46 . A similar prevalence (37 out of 35,000, 0.11%, or 1 in 1,000) in ASO implants worldwide was noted 44 47 . The data were examined by the Review Board and AGA Medical (AGA 2006); these reviews indicated that the device erosion may be associated with over-sizing of the device and recommended that a device size more than 1.5 times the TEE/ICE diameter size of the ASD should not be used for closure of the defect.…”
Section: Ostium Secundum Asdssupporting
confidence: 69%
See 1 more Smart Citation
“…Migration of the device along with erosion of the aorta during follow-up was detected in 18 out of 15,900 (0.12% or 1 in 1,000) ASO implantations in a US study 45 , 46 . A similar prevalence (37 out of 35,000, 0.11%, or 1 in 1,000) in ASO implants worldwide was noted 44 47 . The data were examined by the Review Board and AGA Medical (AGA 2006); these reviews indicated that the device erosion may be associated with over-sizing of the device and recommended that a device size more than 1.5 times the TEE/ICE diameter size of the ASD should not be used for closure of the defect.…”
Section: Ostium Secundum Asdssupporting
confidence: 69%
“…Wire frame fractures were observed in 8% of patients. A more recent analysis of 435 patients in the USA revealed composite clinical success in 93% of patients at 12-month follow-up 44 . The Gore HELEX ® device is generally thought to be a suitable device for the closure of small to medium-sized defects.…”
Section: Ostium Secundum Asdsmentioning
confidence: 99%
“…At 6 month follow‐up 368/400 GSO subjects and 253/271 HELEX subjects were evaluated for clinical defect status, total 621 subjects. The remaining 50 subjects failed to undergo 6 month echocardiography.…”
Section: Resultsmentioning
confidence: 99%
“…Gore & Associates, Flagstaff, AZ) are thought to have a low risk for erosion: their frame can splay around the aorta without exerting significant force toward the aortic root or atrial roof . Long‐term follow‐ups regarding the Gore Helex Septal Occluder have revealed neither erosion nor perforation . As there has been no such mid‐ or long‐term follow‐up data forthcoming on the updated version, the Gore Septal Occluder (GSO), we initiated this retrospective pediatric multicenter study to assess the GSO's clinical performance at midterm follow‐up (GSO in situ ≥12 months).…”
Section: Introductionmentioning
confidence: 99%